2024
DOI: 10.3390/molecules29030682
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Non-Destructive Differentiation of Different Varieties of Rice by Fluorescence Hyperspectral Technology Combined with Machine Learning

Zhiliang Kang,
Rongsheng Fan,
Chunyi Zhan
et al.

Abstract: A rice classification method for the fast and non-destructive differentiation of different varieties is significant in research at present. In this study, fluorescence hyperspectral technology combined with machine learning techniques was used to distinguish five rice varieties by analyzing the fluorescence hyperspectral features of Thai jasmine rice and four rice varieties with a similar appearance to Thai jasmine rice in the wavelength range of 475–1000 nm. The fluorescence hyperspectral data were preprocess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…In conclusion, the presented research offers a methodology for visible spectroscopy through integrating polynomial regression with machine learning algorithms. The results demonstrate the effectiveness of this approach in accurately predicting the dominant The original wavelengths (in nm) for various vapour lamps are as follows: sodium (589), neon (588.2), copper (578.2), mercury (546.074), and helium (587.562) [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In conclusion, the presented research offers a methodology for visible spectroscopy through integrating polynomial regression with machine learning algorithms. The results demonstrate the effectiveness of this approach in accurately predicting the dominant The original wavelengths (in nm) for various vapour lamps are as follows: sodium (589), neon (588.2), copper (578.2), mercury (546.074), and helium (587.562) [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 76%
“…Kang et al [22] reported that the machine learning-assisted fluorescence hyperspectral technique was beneficial for classifying rice varieties. Blake et al's [23] literature review on machine learning methods for cancer classification using Raman spectroscopy data highlighted the popularity of deep learning models, the need to address methodological challenges, and the need for benchmark datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The utility of fluorescence spectroscopy has also been harnessed for the differentiation of rice cultivars [26]. Yang et al advocated for the application of Laser-Induced Fluorescence (LIF) in conjunction with a multivariate analytical approach, incorporating Principal Component Analysis (PCA) and Support Vector Machine (SVM), to distinguish various paddy rice varieties [27].…”
Section: Introductionmentioning
confidence: 99%